Separating Bayesian updating from non-probabilistic reasoning: An experimental investigation - Dan Levin; James Peck; Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2015)
Through a series of decision tasks involving colored cards, we provide separate measures of Bayesian updating and non-probabilistic reasoning skills. We apply these measures to (and are the first to study) a common-value Dutch auction. This format is more salient than the strategically equivalent first-price auction and silent Dutch formats in hinting that one should condition one's estimate of the value on having the highest bid. Both Bayesian updating skills and non-probabilistic reasoning skills are shown to help subjects correct for the winner's curse, as does the saliency of the active-clock Dutch format.
Keywords: D4; D7; D8; 330; Bayesian updating; Non-probabilistic reasoning; Dutch auction